Natural variation in a type-A response regulator confers maize chilling tolerance - Rong Zeng; Zhuoyang Li; Yiting Shi; Diyi Fu; Pan Yin; Jinkui Cheng; Caifu Jiang; Shuhua Yang (Nature Communications, 2021)
The genetic basis of low-temperature tolerance in maize is unclear. Here, the authors show that the type-A Response Regulator 1 (ZmRR1) and mitogen-activated protein kinase (MPK8) are positive and negative regulators of maize chilling tolerance, and ZmRR1 is phosphorylated by ZmMPK8 during cold treatment.